Identity, nationhood and body politics: pathways into the Yemeni world of they die strangers - Yahya Al-Wadhaf; Noritah Omar (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2007)
This article focuses on the Yemeni novel, a purely late 20th century phenomenon which emerged recently following the Yemeni revolution in 1962 and the emergence of the modern nation state in Yemen. However, this new form suffers from serious marginalization in contemporary postcolonial studies. The novel‟s appearance in English in 2001 serves many literary and cultural purposes. Taking the cultural particularity and marginalization of Yemen into account, the novel is both informative and imbued with meanings that participate in and contribute to the process of creating new identities of literacy practices by offering new horizons for reading multicultural literary texts such as the Arabic novel. This article evaluates the novel They Die Strangers (1972) by the Yemeni novelist Mohammed Ahmed Abdul Wali as a postcolonial narrative of emigration in which the writer argues about what is called the ideology of return. An emigrant himself, the writer discusses the impact of long-term emigration on the individual, his family and the society as a whole. The discussion, using a postcolonial perspective, covers issues related to the construction of the Yemeni identity, body politics, the Yemeni farmers‟ dream and the representation of women focusing on the body-land association. The discussion concludes with considering the novel as a parody against those who migrate leaving their women and their land behind, only to live and die as strangers.